MEGATRENDS OF GLOBAL DEVELOPMENT (Вісник: Міжнародні відносини, 2024)
This study identifies and analyses megatrends of global development and how conceptual and applied aspects of this megatrends are treated in the expert-academic community by outlining the specifics of megatrends of global development in the international political sphere. Megatrends of global development such as the cyber revolution, the transition to information society based on the production and consumption of information, the growing role of network structures, on world politics, increasing consumption, hyper-consumption as a complex systemic phenomenon have a significant impact on world politics.The paper summarises the megatrends of global development that will shape the world in future. The "compression" of historical and political time as a megatrend of global development is reflected in the increase of the intensity of historical events and the decrease in the duration of historical and political cycles. There is a threefold transformation of the modern political organisation of the world: the transformation of the Westphalian world political model, which is determined by globalisation as a megatrend of global development, the transformation of the modern international system, largely due to integration as a megatrend, and the transformation of political systems. A change in the hierarchy of leading international actors, a crisis in the institution of global leadership, a rethinking of the power of leading global actors, and the emergence of new potential political and economic global leaders are projected.
Keywords: global development, international system, megatrends, international relations, world policy, world order